OPTIMIZATION OF WORK CULTURE THROUGH THE "SI PEN" PERFORMANCE MONITORING APPLICATION IN THE FIELD OF FIREFIGHTING AND RESCUE IN THE MAHAKAM ULU REGENCY AREA - Stevanus Garuda; Dandan Haryono; Irwan Waris (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the optimization of work culture through the implementation of the Performance Monitoring System (SI PENA) performance monitoring application in the Fire and Rescue Department of Mahakam Ulu Regency. The background of the study is based on the need for public organizations to improve the effectiveness of apparatus performance through digital innovation that not only functions as a monitoring instrument, but also as a catalyst for work culture change. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and document reviews. Research informants include the Head of Division, Head of General and Personnel Sub-Division, Fire Department staff, and Regional Secretariat officials. The research results show that SI PENA has had a positive impact on the five dimensions of Electronic Performance Monitoring (EPM): purpose, invasiveness, constraints, target control, and synchronicity. This application effectively strengthens transparency, accountability, and real-time reporting synchronization, although it still faces challenges such as limited digital infrastructure and employee psychological resistance due to the feeling of being monitored. From a work culture perspective, SI PENA has been proven to encourage increased discipline, openness, mutual respect, and cooperation among employees. Thus, this application functions not only as a performance monitoring tool, but also as an instrument that strengthens the values of the organization's work culture. The study's conclusions confirm that optimizing work culture through SI PENA requires adaptive policy support, increased staff capacity, and strengthened information technology infrastructure. The practical implications of this research are the need to integrate technology, organizational culture, and leadership to strengthen public sector performance.